1969
DOI: 10.1002/aic.690150510
|View full text |Cite
|
Sign up to set email alerts
|

Thermally induced solid state polycondensation of nylon 66, nylon 6‐10 and polyethylene terephthalate

Abstract: The mechanism of solid state polycondensation has been subjected to a fundamental analysis. Equations were formulated for combined diffusion and chemical reaction for two separate situations. One was for solid state polycondensation in polymer flakes or chips. The other dealt with polymer powders. The resultant solutions related molecular weight changes to rote functions. A technique for deriving the rate functions from experimental data is described.Solid state polycondensations were then studied for nylon 66… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
48
0

Year Published

1990
1990
2011
2011

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 88 publications
(49 citation statements)
references
References 8 publications
1
48
0
Order By: Relevance
“…The mass density of polymer is uniform through out the particle. However, the concentration of polymer end groups changes due to the polycondensation reaction and the time rate of change can be represented as and z = zo + ( e , -e ) / 2 = 1 -e / 2 (8) where A = 0 for a plane sheet, 1 for a cylinder, and 2 for a sphere. Note that in eqs.…”
Section: Model Development For Solid State Polycondensation Processmentioning
confidence: 99%
See 1 more Smart Citation
“…The mass density of polymer is uniform through out the particle. However, the concentration of polymer end groups changes due to the polycondensation reaction and the time rate of change can be represented as and z = zo + ( e , -e ) / 2 = 1 -e / 2 (8) where A = 0 for a plane sheet, 1 for a cylinder, and 2 for a sphere. Note that in eqs.…”
Section: Model Development For Solid State Polycondensation Processmentioning
confidence: 99%
“…(23) and using eq. (8), we obtain Equation (29) assumes that the diffusivity is a function of reaction time, since the polymer starts crystallizing as it builds up its molecular weight. The nonuniform profile of the molecular weight within the particle implies variation in crystallinity as a function of distance from the interface of the particle.…”
Section: Case 2 Diffusion-controlled Processmentioning
confidence: 99%
“…For example, Srinivasan et al [1] found that SSP of nylon 66 fibers at and above 220 8C follows step-growth bulk polymerization kinetics. Chen et al [2] found that the SSP of nylon 66 flakes was reactioncontrolled. Tang et al [3] developed a reaction-diffusioncontrolled model for SSP of PET.…”
Section: Introductionmentioning
confidence: 99%
“…An early attempt to describe SSP in single polymer particles considered only diffusion of the condensate and neglected reaction kinetics. 7 Recently, several research groups 8 -10 have developed kinetic models for the solid-state polymerization of PET and have investigated the effects of condensate (ethylene glycol) diffusion on the molecular-weight evolution. Other aspects of the SSP of PET have also been examined, such as the effect of particle size, 9,[11][12][13][14] the type of purge gas, 15 the flow rate of purge gas, [12][13][14] and the use of plasticizers to increase the rate of polycondensation.…”
Section: Introductionmentioning
confidence: 99%